Factors affecting cryopreservation-associated damages in sperm motility of cockerels (Gallus gallus domesticus). Issue 1 (2nd January 2023) - Sushadi, P. S.; Kuwabara, M.; Iimura, H.; Asano, A.
ABSTRACT: 1. Sperm are exposed to severe osmotic stress during cryopreservation, which results in impairment of fertilisation ability, including motility and viability, in poultry. Sperm osmotolerance is regulated by many extracellular factors and varies widely in birds, leading to uncertainty in the nature of the osmotic injury. 2. Tail bending is a primary response resulting from cell swelling from excessive osmotic stress. However, the underlying mechanism responsible for tail bending is largely unknown. This study examined the relationship between osmotic stress and post-thaw motility, with a particular focus on the role of Na + /K + ATPase (NKA) in the tail bending response. 3. Cryopreserved sperm exhibited rapidly reduced motility when maintained at 37°C. The combination of temperature change and osmotic stress was a primary factor responsible for tail bending. This work tested a hypothesis known to be associated with post-thaw tail abnormality in other species and found that cold shock, that is not accompanied by an apoptotic response, may occur. Ouabain inhibition of Na + /K + ATPase activity alleviated the tail bending response in fresh and post-thaw sperm. 4. These results demonstrated that the combination of temperature change and osmotic stress has a primary impact on the reduction of post-thaw motility, with a particular role in NKA activity, in the tail bending response of chicken sperm. These results provide a foundation for establishing cryopreservation methodology to ensure the optimal fertilisation potential of cryopreserved chicken sperm.